2012
DOI: 10.1371/journal.pone.0039452
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Change and Disease Dynamics: Effects of Intensive Forest Management on Puumala Hantavirus Infection in Boreal Bank Vole Populations

Abstract: Intensive management of Fennoscandian forests has led to a mosaic of woodlands in different stages of maturity. The main rodent host of the zoonotic Puumala hantavirus (PUUV) is the bank vole (Myodes glareolus), a species that can be found in all woodlands and especially mature forests. We investigated the influence of forest age structure on PUUV infection dynamics in bank voles.Over four years, we trapped small mammals twice a year in a forest network of different succession stages in Northern Finland. Our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 54 publications
(72 reference statements)
3
57
1
Order By: Relevance
“…In summer, reproduction in disturbed habitats, such as clear-cuts, could be as high as in old forest or even higher (Ecke et al 2002). Voutilainen et al (2012) found that PUUV infection rate of bank voles was higher in young than in old forest habitats. However, since the population density of bank voles was highest in old forests, these habitats had higher densities of PUUV infected voles (Voutilainen et al 2012).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In summer, reproduction in disturbed habitats, such as clear-cuts, could be as high as in old forest or even higher (Ecke et al 2002). Voutilainen et al (2012) found that PUUV infection rate of bank voles was higher in young than in old forest habitats. However, since the population density of bank voles was highest in old forests, these habitats had higher densities of PUUV infected voles (Voutilainen et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Nephropathia epidemica (NE) is a milder variant of HFRS caused by the hantavirus Puumala virus (PUUV) present in many parts of Europe (Olsson et al 2010), and bank voles (Myodes glareolus) are the natural reservoir (Brummer-Korvenkontio et al 1980, Yanagihara et al 1984. The epidemiology of NE is closely linked to the temporal and spatial dynamics of the bank vole (Niklasson et al 1995, Olsson et al 2005, Voutilainen et al 2012. In Sweden, approximately 90% of all diagnosed cases are found in the northern part of the country .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that individual variations of immune gene expression could reinforce these differences in the epidemiological roles of particular bank vole groups within natural populations. In particular, males, through higher capacities to replicate, excrete PUUV, and to perform long-distance dispersal (Kozakiewicz et al, 2007), could have key roles in spreading PUUV within the landscape (Deter et al, 2008a;Voutilainen et al, 2012). The lower expression of Mx2 gene detected in immature voles could also have important epidemiological consequences for PUUV transmission.…”
Section: Intrinsic Factors Shaping Immunoheterogeneitymentioning
confidence: 99%
“…The annual incidence of NE in humans can be explained with high degree (84% of variability) by density of M. glareolus in autumn and the number of rainy days in winter (Khalil, Olsson, et al., 2014). In contrast, the number of PUUV‐infected bank voles and PUUV prevalence (the proportion of infected bank voles) has been shown to be affected by habitat type (Magnusson, Ecke, et al., 2015; Voutilainen et al., 2012). …”
Section: Introductionmentioning
confidence: 99%